Atmospheric Carbon and Food Security in Nepal - Karki, Krishna B. (Journal of Agriculture and Environment, 2009)
Release of carbon from soil system is inevitable. It is increased through emission breath by animals, burning of fossils fuel, biomass burning and intensive agriculture. The only question is how to absorb that carbon in the atmosphere and reduce the carbon content of the atmosphere. Increase of CO2 in atmosphere increases the crop yield due to high photosynthesis, but the crops should tolerate increased temperature caused by higher CO2 concentration. Increase of soil organic matter through the addition of organic manure is one of the options that the carbon is retained temporarily, but in the long run because of oxidation and reduction process in soil, carbon will ultimately release to the atmosphere. Absorption of CO2 by the plants is one of the options, which is known as sequestration to mitigate increased carbon in the atmosphere. Key words: Climate change; Carbon sequestration; CO2 in atmosphere and crop yield; etc. The Journal of Agriculture and Environment Vol:.9, Jun.2008 page: 54-61